Someone, no one : an essay on individuality - Burridge, Kenelm (Princeton legacy library., 1979)
Examining the concept of individuality and the ideology of individualism in terms of a dialectic between the self and the social order, the author draws a distinction between the person as an identity-a "someone"-who conforms to social roles and norms, and the individual as a nonidentity-a "no one"-who holds particular nonconformist perceptions of truth that result in conscious and independent moral discrimination and innovation.Originally published in 1979.The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.